"Swimming against the tide": conditional discharge from medium secure care. Issue 2 (20th February 2020) - McDonnaugh, Tanya; Underwood, Alan; Williams, Amanda
Abstract : Purpose: The purpose of this paper is to explore the experiences of mentally disordered offenders (MDOs) conditionally discharged from secure hospitals on a restrictive Section of the Mental Health Act (Section 37/41). Design/methodology/approach: Data were derived from seven semi-structured interviews from three forensic community teams. Findings: Thematic analysis identified seven predominant themes: (1) the uncertainty of the discharge timeframe; (2) fear of jeopardising discharge; (3) progress; (4) engagement with community life; (5) barriers to social engagement; (6) evolving identity and (7) someone to turn to. Findings are discussed in relation to the recovery model and the good lives model. Practical implications: The findings highlight the importance of fostering trust between MDOs and their care teams to encourage help-seeking. They also suggest that resources should be sequenced appropriately throughout the discharge process, to match the "window of engagement" and maximize impact and effectiveness. Originality/value: This research gained rarely obtained first-hand perspectives from MDOs, with the findings contributing to a more effective evaluation of the discharge pathway.